Gaining Competitive Advantage by Streamlining Bureaucracy:: A Lesson for Developing Countries - Muczyk, Jan; Saber, Hussien (Journal of Comparative International Management, 2001)
More and more of the developing countries are seeking membership in the World Trade Organization. One of the consequences of WTO membership is the necessity of competing with the "best-in-class" companies in the international marketplace. Unfortunately, many developing countries are plagued by archaic bureaucracies, which constitute a major impediment to competitiveness, at a time when it is crucial for developing countries to create a vibrant private sector in order to assimilate the large numbers of new entrants into the workforce. This paper attempts to identify the causes of bureaucracy and the ways by which organizations can de-bureaucratize. Although intense competition is by far the best prescription for de-bureaucratizing, other strategies must also be pursued simultaneously. The economies that will prosper in the future are the ones that will be able to re-invent themselves periodically, something that bureaucratic societies find difficult to do.